Repetition in surat AL-Aaraf-: an analytical rhetorical study - Wasseg, Ahmed Batal (Al-Adab Journal, 2022)
Praise be to God, Lord of the Worlds, and prayers and peace be upon the master of creation, Muhammad, and upon his pure and pure family and his chosen companions. The Qur’anic text is one of the most important texts in which the sciences of the Arabic language were applied in its best form. From here, I chose the Qur’anic text for this study. I have chosen the method (repetition) in the Holy Qur’an; Due to its abundance in the Qur’an and the fact that it carries various rhetorical and semantic purposes, I chose Surat Al-A’raf; For the sufficiency of this surah and for its inclusion of most types of repetition, my research was under the title ((Repetition in Surat Al-A’raf - an analytical rhetorical study)). I divided my research into a preface and two chapters, the preface came under the title (Repetition), in which I presented repetition in language as well as repetition in terminology as well as repetition in the rhetorical and grammatical heritage. I presented the place of repetition in contemporary textual studies. The first topic came under the title (repetition in the word) in which I presented two types of repetition, one of them (the explicit repetition of the word) and the other (repetition in the derivation of the word), then the second topic came under the title (repetition in the sentence). Blessed customs by analyzing the texts presented by a full rhetorical analysis. The researcher reached many and varied results, including: 1-Repetition is one of the old and modern topics that cannot be dispensed with. This is due to its importance in ancient and contemporary rhetorical studies as well as textual studies> 2- The texts of repetition in Surat Al-Araf presented many different arts of rhetoric in its three sciences (Al-Ma’ani, Al-Bayan, Al-Badi’) 3- We found in (explicit repetition) that the repetition of verbs has increased at the expense of repetition of nouns, as well as the case in (derivative repetition), and we have sometimes found repetition between the noun and the verb, in addition to that, we have also noticed the diversity in verbs, especially between the imperative and the present in addition to There is a lot of agreement in the matter, as we have indicated While we found the parallel between nouns and verbs in the repetition of sentences as well as the repetition of letters, the repetition of the sentences that was presented in the second topic was most of the sentences including the noun, the verb and the letter, and when these sentences were repeated the noun, the verb and the letter were repeated. 4-Some of the constructional methods (order) contributed to the eloquence of the text of repetition, including (the command, the prohibition, the reprimanded declarative interrogation, the declarative question, the plea) in addition to the large number of affirmative reports in the texts of repetition. primary, and the reason for the large number of confirmed news, as the researcher sees; Because Surat Al-A’raf is one of the Meccan surahs and the Meccan surahs are directed at all humans, and most of them deny what the Qur’anic text presents. 5- There was a lot of connection between the texts of the sentences of repetition in Surat Al-Aaraf with the types of repetition presented, and most of the connection was in the agreement of the sentences in the creation (the request). This affected the repetition texts; Because it linked the text with the other text, especially since the connection has increased in the same repetition sentences as in the repetition of verbs (the command) or (the prohibition). The chapter has been reduced in these texts and from it (the almost perfect communication, the difference between the composition and the report), and the reason for this lack is due to the agreement of most of the sentences in the composition, as we said, especially that the surah is Meccan and contains many commands and prohibitions. In addition to the link, we found other linking tools, including the adverbial link (time), which was mentioned in the tool (then). 6-The texts of repetition carried a lot of topics that are included in the science of semantics for the sake of the language of the text and its specialization and attention to the most important, and this was represented in (advance and delay, shortening, omission) and others. In addition to the presence of graphic arts that contributed to the approximation of the image presented by the repetition text through (similarity or metaphor). It remains to say here that (contradiction) has dominated many of the texts of repetition in Surat Al-A’raf, especially in the prohibitions that presented what God has provided and what humans offer, or between God’s data for humans and Satan’s data for humans himself; He contributed to clarifying the difference between those who want to benefit people and those who want to harm them. 7-Too much (repetition of the word) at the expense of (repetition of sentences); Due to the diversity of events in Surat Al-A’raf, as well as the fact that the repetition of the word can occur significantly in one verse, while the repetition of sentences decreases in the verse and increases in the multiple verses.